Echocardiographic predictors of outcome after isolated tricuspid valvular surgery. (4th February 2022) - Eggenspieler, F; Huttin, O; Erpelding, ML; Filippetti, L; Pace, N; Popovic, B; Sirbu, C; Elfarra, M; Maureira, P; Selton Suty, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Right ventricular (RV) function is one factor influencing outcome after isolated tricuspid valve surgery (ITVS). As it is highly load dependant, its echocardiographic assessment requires a multiparametric analysis. Purpose: To assess prognostic value of RV echocardiographic parameters among patients undergoing ITVS. Methods: Preoperative echocardiograms were retrospectively reviewed in 75 patients (mean age 54 ± 17 years) who underwent ITVS between 2007 and 2020. We assessed classical parameters of RV load, morphology and function, and calculated a load-remodeling-function index (LRFI) combining load (using tricuspid regurgitation time-velocity integral), remodeling (using ratio of RV diameter / length) and function (using strain rate (SR)). Those parameters were compared between alive and dead patients at 1-year follow-up. Results: Mortality rate was 17.3% at 1 year and 22.7% at 5 years. Among standard RV function parameters, only S' and SR were significantly lower in dead than in alive patients at 1 year. LRFI was significantly higher in dead patients at 1-year. By analysis of ROC curve, LRFI (AUC 0.823 [0.678-0.968]; p = 0.002) was the best predictor of death at 1 year. When associating a clinical variable (pre-existing right heart failure (RHF)) and LRFI, Kaplan Meier curves showed significantly higher mortality in patients with both RHF and altered LRFI. Conclusion: Global RV analysis using a parameter combining load, remodeling and function may help in the prognostic assessment of patients undergoing ITVS, in addition to the presence of RHF.